Prioritization of low food grains productivity districts for rural development planning in India - Meena, Dinesh Chand; Kumari, Maina (Indian Farming, 2024)
Agriculture is the mainstay of many rural economies, ensuring food and nutritional security, employment, livelihoods, and economic development. The agricultural productivity of a country plays a crucial role in determining its people's prospects, as it significantly contributes to eradicating hunger, poverty, and inequality. Despite the remarkable growth of the agriculture sector, there is still a need for increased agricultural productivity in several districts and agro-climatic zones (ACZs). One hundred twenty-two districts yield less than 1.5 t/ha food grain productivity. Therefore, prioritizing districts with low food grain productivity is crucial to bringing underdeveloped ones into development.